Epilepsia partialis continua present with shoulder joint-trunk-hip joint rhythmic clonic seizure: a case report - Lv YD (Dove Medical Press, 2016)
Yudan Lv, Zan Wang, Fengna Chu, Chang Liu, Hongmei Meng Department of Neurology and Neuroscience Center, The First Hospital of Jilin University, ChangChun, People’s Republic of China Abstract: Epilepsia partialis continua (EPC) is a particular type of epilepsy which is distinguished from “common epilepsy” by its characteristic semiological features. However, unusual manifestations should be described in order to give awareness at clinical diagnosis. In this case report we describe a rare EPC case not previously reported, in which left shoulder joint-trunk-hip joint jerk was present for 1 week. Abnormal electroencephalogram and cerebrospinal fluid results supported a diagnosis of viral encephalitis. Antiepileptic treatment seemed effective. Our report emphasizes that a detailed functional anatomical analysis and synchronized electroencephalogram discharge should be done to avoid misdiagnosis in patients with synchronic shoulder-trunk-hip jerk symptoms. Keywords: EPC, shoulder-trunk-hip, EEG, clonic seizure, virus encephalitis